Peranan Pertanian Sistem Arealan dan Penanggulangan Kemiskinan di Pedesaan (Studi Kasus Desa Manukan Kecamatan Kalitidu Kabupaten Bojonegoro) - Pamungkas, Luky Handianto Adi; Susilo, Susilo; Pratama, Yogi Pasca (Jurnal Ilmu Ekonomi dan Pembangunan, 2015)
Most of the people of Manukan village, Bojonegoro regency, have livelihoods as farmers or as farm laborers. Floods that always come in every rainy season have destroyed hectares of rice fields ready for harvest. This is what causes poverty in Manukan village to be difficult to overcome. However, since the new irrigation system was discovered for rice farming in Manukan village called the Arealan System, precisely since 1997 the condition of community welfare in Manukan village gradually lifted. The use of agricultural systems in crops in terms of quality and quantity can be significantly improved.The purpose of this research is to know how far the role of paddy farming Arealan to poverty alleviation in Manukan village. The results of this study indicate that using the paddy system of farmers in Manukan village can increase rice yield in terms of quality and quantity. So with the increase in the quantity and quality of rice produced will increase the income obtained by farmers. Keywords: Arealan Paddy Farming System, Poverty Alleviation, Bojonegoro District Government Role.JEL Classification:  I31. Q13